PENALARAN MATEMATIS MAHASISWA DALAM MEMECAHKAN MASALAH ANALISIS REAL BERDASARKAN KEMAMPUAN BERPIKIR INTUITIF - Adamura, Fatriya; Susanti, Vera Dewi (Universitas Sebelas Maret, 2018)
Abstract: Mathematical reasoning ability is needed by students both in the process of understanding mathematics and in everyday life context. In fact, Indonesian students’ ability in the field of mathematics is still very low. Referring to the fact, this study is attempted to determine students' mathematical reasoning in solving real analysis problems based on their ability to think intuitively. This study is a qualitative descriptive research. The data sources in this study are college students. Data are collected through written tests and interview. Data analysis in this study is carried out by stages of data reduction, data presentation, and conclusion. The results show that (1) Students with high intuitive thinking skills in real analysis problem solving have a tendency to implement mathematical reasoning perfectly. They are able to carry out mathematical reasoning at each stage of solving real analysis problems. (2) Students with medium intuitive thinking ability in solving real analysis problem have a tendency to implement mathematical reasoning less perfectly. They are not able to carry out mathematical reasoning at the stage of solving problems according to plan and re-checking it again. (3) Students with low intuitive thinking skill in solving real analysis problem have a tendency to implement mathematical reasoning imperfectly. They are unable to carry out mathematical reasoning at the stage of planning solution and solving problem.Keywords:mathematical reasoning, solving problem, intuitive.